2021
DOI: 10.1093/braincomms/fcab083
|View full text |Cite
|
Sign up to set email alerts
|

Defining functional variants associated with Alzheimer’s disease in the induced immune response

Abstract: Defining the mechanisms involved in the aetiology of Alzheimer’s disease from genome-wide association studies alone is challenging since Alzheimer’s disease is polygenic and most genetic variants are non-coding. Non-coding Alzheimer’s disease risk variants can influence gene expression by affecting miRNA binding and those located within enhancers and within CTCF sites may influence gene expression through alterations in chromatin states. In addition, their function can be cell-type specific. They can function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…The fourth replicated protein, poliovirus receptor ( PVR ), has multiple roles in the immune response, including mediating NK cell adhesion and triggering their effector functions. PVR has been found to be associated with bipolar disorder, schizophrenia [ 39 ], and Alzheimer’s disease [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fourth replicated protein, poliovirus receptor ( PVR ), has multiple roles in the immune response, including mediating NK cell adhesion and triggering their effector functions. PVR has been found to be associated with bipolar disorder, schizophrenia [ 39 ], and Alzheimer’s disease [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed colocalization with only two of these loci: 1) between AD and the expression of FNBP4 in memory B cells (H4 = 0.913) and in CD8+ T cells (H4 = 0.85 and 0.84, for effector and naïve CD8+ T cells, respectively), and 2) between PD and the expression of ARSA in CD8+ effector T cells (H4 = 0.88). FNBP4 (situated approximately 15,000 base pairs away from CELF1) has been previously identified as an AD risk locus (Karch et al, 2016), but in a more recent transcriptome-wide association study (TWAS) of AD, this gene was discarded in conditional analyses (Harwood et al, 2021). ARSA has been previously investigated as a PD risk locus in a Chinese population, in which no significant associations were found with PD susceptibility (Pan et al, 2022).…”
Section: Gene Expression Levels Of Immune-related Genes Share Causal ...mentioning
confidence: 99%
“…To link our preclinical findings in adipose tissue to humans, we overlapped adipose tissue DEGs in the different mice models and with adipose tissue DEGs of women with PCOS (Divoux et al, 2022). The result showed that altered MS4A6E gene expression is shared by all PCOS-like models, a gene that has been shown to be involved in neurodegenerative disorders (Harwood et al, 2021) . Moreover, we found that adult androgen programming has highest number of common DEGs between the ovary and adipose tissue with the lowest number of common DEGs in maternal obesity followed by PNA mouse models.…”
Section: Transcriptomic Interaction Among Hypothalamus Ovary Adipose ...mentioning
confidence: 99%